Business internationalisation in the basque country, does public financing influence in the results? - Bilbao, Enara Zarrabeitia (2015)
Currently, almost all the territories consider the internationalisation of their enterprises as a key enabler to realize their competitiveness, welfare and regional development. However, so far, very few studies have been conducted that analyze the relationship between the internationalisation aids and the degree of internationalisation achieved by a territory. Thus, the objective of this research paper is to analyze the relationships between the internationalisation indicators and the budget expenditure devoted to internationalisation by Basque government. This requires definition of the indicators for assessing the internationalisation, which have been obtained from the Plan for Business Competitiveness 2010-2013 and the Plan for Business Internationalisation 2014-2016 elaborated by Basque Government. Moreover, in order to carry out the research study, the necessary data has been obtained from different Basque and Spanish institutions. After obtaining the data, the estimation method used has been a bivariate correlation analysis that has helped to achieve the target set in the investigation. Results shows that there is a positive relationship between the expenditure on business internationalisation and the main indicators studied, but the same is not true, however, for the degree of openness of the economy and the investment relations with foreign countries. The article provides new information on how the government of a small region, such as the Basque Country, perform in relation to the internationalisation policies.